Approaches to Training Computer Specialists in the Context of Non-Formal Education - Lysenko, S. (Problems of Engineer-Pedagogical Education, 2023)
The significance of the research topic arises from the imperative to address the specific cognitive and professional enquiries of students. This necessitates substantial modifications across the organizational, procedural, and content-technological underpinnings of the educational environment. Education institutions are actively engaged in tackling this challenge. Among the foremost modalities for addressing the individual vocational and educational needs of numerous professionals within the computer industry, the system of instruction within non-formal educational settings stands out. This article centers on dissecting the fundamental aspects of individualization, differentiation, and personalization in education, with the aim of ascertaining the viability of their integration into the non-formal training of computer specialists. The study employs theoretical research techniques, including analysis, generalization, and systematization. The findings illuminate that the utilization of individualized education is circumscribed by substantial constraints, encompassing intricate diagnostic processes, the demand for prolonged and multifaceted influence on the learner's persona, and the extent of instructor involvement. These constraints stem from the distinctive nature of instruction within non-formal education institutions and the competences of educators, who are predominantly practicing industry specialists rather than professional pedagogues. Findings show that differentiated learning is beneficial only under specific conditions, dictated by factors such as group dynamics, structure of practice-oriented curriculum, and the number of students in an academic group. The viability of personalized learning, rooted in a specialist's vocational activity, is meticulously substantiated. Determinants for the implementation of personalized learning encompass the modality of instruction (on-thejob training, dual education, blended learning, distance learning, and traditional (in-class) learning), curriculum nuances (core substantive elements, supplementary components for cultivating qualities or knowledge from cognate domains), digital repository or cloud-based educational environment, the tenets of the process and outcome monitoring system for educational progress (ongoing and final assessment), and the functions of the educational platform facilitating information aggregation and student interaction. Future research endeavors should focus on the establishment and elaboration of a systematic methodology for the personalized instruction of computer specialists within the framework of non-formal education settings.